Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Pengungkapan Corporate Social Responsibility (CSR) - Putra Putra; Mia Angelina Setiawan (Universitas Negeri Padang, 2022)
This study is a quantitative study that aims to obtain empirical evidence regarding the effect of profitability, leverage, and firm size on the disclosure of corporate social responsibility (CSR) in manufacturing companies. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2020 for 5 years. This study uses purposive sampling method in selecting the sample, with a total sample of 385 samples. The type of data in this study is secondary data obtained from the Indonesia Stock Exchange in the form of an annual report. Analysis of the data used is multiple regression analysis. The results of this study indicate that profitability and leverage have no significant effect on the disclosure of corporate social responsibility, while the size of the company has a significant and positive effect on the disclosure of corporate social responsibility.